THE INFLUENCE OF PERSONALITY ON ENTREPRENEURIAL INTENTIONS - Sugiyanto Sugiyanto (UPMI Management, 2021)
The role of higher education is vital in giving birth to new entrepreneurs in Indonesia. The emergence of many new entrepreneurs has an impact on the development of the country's economy. These impacts include creating jobs and increasing regional and state income. This article provides a discussion of self-personality as a predictor of entrepreneurial intention with self-efficacy as mediation. A personality is a form of character and trait, which can shape behavior. The personality dimensions used in this study are conscientiousness and openness to new experiences. This study used a sample of 210 students from several universities in the city of Surakarta, Indonesia. Data collection techniques, using a purposive sampling method. Data analysis, using path analysis with the help of Structural Equation Model (SEM). This study's findings indicate that self-efficacy mediates the effect of openness to new experiences on entrepreneurial intention. However, conscientiousness has not been shown to affect interest in entrepreneurship.